2014
DOI: 10.1111/j.1728-4465.2014.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unmet Need and Unwanted Childbearing: Evidence from a Panel Survey in Pakistan

Abstract: Pakistan's high unmet need for contraception and low contraceptive prevalence remain a challenge, especially in light of the country's expected contribution to the FP2020 goal of expanding family planning services to an additional 120 million women with unmet need. Analysis of panel data from 14 Pakistani districts suggests that efforts to reduce unmet need should also focus on empowering women who are currently practicing contraception to achieve their own reproductive intentions through continuation of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Major demographic survey programmes (e.g., the Demographic and Health Surveys [DHS], the Multiple Indicator Cluster Surveys [MICS]) have relied on three items: an item asking for the woman’s ideal number of children (ideal family size); an item asking about her desire to have another child, and the desired timing of the next birth (prospective preferences); and an item asking whether current pregnancies or recent births were wanted, mistimed or unwanted (retrospective desires). Many studies have demonstrated the relatively high validity and reliability of the prospective preferences item, including its predictive validity [ 12 15 ], and therefore the now-standard survey-based indicator of unmet need for contraception relies on this item [ 16 ]. But the standard indicator of unmet need also relies on the retrospective report of whether current pregnancies and recent births were wanted and on time, and empirical evidence raises serious questions about the validity and reliability of this item [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major demographic survey programmes (e.g., the Demographic and Health Surveys [DHS], the Multiple Indicator Cluster Surveys [MICS]) have relied on three items: an item asking for the woman’s ideal number of children (ideal family size); an item asking about her desire to have another child, and the desired timing of the next birth (prospective preferences); and an item asking whether current pregnancies or recent births were wanted, mistimed or unwanted (retrospective desires). Many studies have demonstrated the relatively high validity and reliability of the prospective preferences item, including its predictive validity [ 12 15 ], and therefore the now-standard survey-based indicator of unmet need for contraception relies on this item [ 16 ]. But the standard indicator of unmet need also relies on the retrospective report of whether current pregnancies and recent births were wanted and on time, and empirical evidence raises serious questions about the validity and reliability of this item [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Population growth in Pakistan presents significant challenges. Contraceptive prevalence rates (CPR) and fertility rates have largely remained unchanged, or have shown slow and insufficient improvements, during the last two decades [ 1 ]. Currently Pakistan has an estimated population of over 190 million people [ 2 ] and is the sixth most populous country [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current FP2020 Initiative focus on reducing unmet need and identifying 120 million new FP users by 2020 [24] may miss the mark by ignoring current users who are motivated to avoid a pregnancy and need a more effective method [17, 25]. These women may be the most likely to resort to abortion if they experience contraceptive failure and an unintended pregnancy [10].…”
Section: Introductionmentioning
confidence: 99%